طرق التعرف على مسرعات الاشتعال وجمعها وتحليلها في الحرائق المتعمدة فى المملكة العربية السعودية - الضياح، عبدالرحمن بن محمد (جامعة نايف العربية للعلوم الأمنية - الجمعية العربية لعلوم الأدلة الجنائية والطب الشرعي, 2015)
إن تحليل مخلفات الحرائق والكشف عن نوع المسرعات المستخدمة فيها عند الاشتباه في وجود حريق متعمد يعد من أهم الفحوصات، فوجود أي آثار محتملة لهذه المسرعات في العينات المرفوعة من مسرح الحادث يعتبر من النقاط الحاسمة في إثبات هل الحريق متعمد وبقصد جنائي أم لا وقسمت هذه الدراسة إلى أربعة أجزاء، في الجزء الأول تم الحديث عن أهم مسرعات الاشتعال المستخدمة في الحرائق المتعمدة في المملكة العربية السعودية ومدى وجودها في مسارح الحريق، وخصص الجزء الثاني من الدراسة لتحديد الطرق المستخدمة في المملكة لجمع وتحريز الآثار المادية الموجودة في مسارح الحريق المشتبه باستخدام مواد مسرعة للاشتعال في المملكة، أما في الجزء الثالث فتم استعراض أبرز التقنيات المستخدمة في استخلاص وكشف بقايا مسرعات الاشتعال المستخدمة في الحرائق المتعمدة في المملكة، بينما في الجزء الرابع تمت مناقشة أبرز المشكلات والصعوبات التي تواجه خبراء ومنسوبي الأدلة الجنائية في المملكة عند رفع وتحريز وتحليل هذه الآثار والتوصيات التي اقترحت لحلها. وكان من أهم النتائج التي توصلت إليها هذه الدراسة أن أكثر مسرعات الاشتعال استخداما لبدء الحرائق المتعمدة في المملكة كان البنزين خصوصا بنزين 91، يليه الكيروسين ثم الديزل وأخيرا التنر (thiner). واتفق المختصون على صعوبة هذا النوع من المسارح خصوصا بعد إطفائه واستلامه من الدفاع المدني، كما أشاروا أيضا على أن أفضل التقنيات المستخدمة لاستخلاص وكشف بقايا مسرعات الاشتعال في حالة العينات الصلبة هو جهاز كروماتوجرافيا الغاز المقترن بحاقن الفراغ الرأسي (GC- Headspace)، أما في حالة العينات السائلة فبالإمكان استخدام جهاز كروماتوجرافيا الغاز المقترن بمطياف الكتلة (GC- MS) أو استخدام مطيافية تحويل فورير للأشعة تحت الحمراء (FT-IR).
If there is a suspicion of arson, analysis of fire debris and identification of potential accelerants is considered to be one of the most essential examinations of the investigation. The existence of any traces of potential accelerants in a sample taken from the fire scene is crucial in determining whether the fire was started deliberately or not. This study is divided into four parts: the first part describes the most important ignition accelerators which are used in arson fires in Saudi Arabia. The second part is devoted to determining the methods that are used to collect and store trace evidences from fire scenes in Saudi Arabia, if there is a suspicion that accelerants have been used to ignite the fire. The most important techniques used in the extraction and analysis of ignitable liquid residue (ILR) in arson cases are presented in the third section. Finally, the fourth part discusses the problems and difficulties which both experts and employees in The General Department of Forensic Evidence in Saudi Arabia face when collecting and sampling traces as well as some recommendations to address these issues. The results obtained from this study indicate that the most common accelerant used to start fires is gasoline, specifically ‘Octane 91’, followed by kerosene, thereafter diesel and finally paint thinner. Experts are also agreed on the difficulty of obtaining evidence from this type of crime scene, especially after the fire has been extinguished and the scene is released for investigation by the Civil Defense. They also agree that the best technique for extracting and analyzing ignitable liquid residue (ILR) in the solid phase should be Gas Chromatography coupled with Headspace (GC-Headspace). In liquid samples, either Gas Chromatography coupled with Mass Spectroscopy (GC-MS) or Fourier transform infrared (FT- IR) can be used.
Keywords: مواد كيميائية -- الحرائق -- السعودية